Cardiac Management in the Frail Elderly Patient and the Oldest Old - Ungar, Andrea; Marchionni, Niccolò (Springer International Publishing : Imprint: Springer, 2017)
This book focuses specifically on the management of cardiovascular disease in elderly patients with particular frailties and in the "oldest old". It is clearly explained how treatment in these patients differs from that in patients in their seventies who respond well to therapies and do not present frailties or organ failures. Although not young, the latter patients can be treated almost like any other patient, according to established guidelines. In contrast, the frail, compromised elderly and the oldest old require specific measures that target their needs, including with respect to underlying renal conditions. The book considers all those pathologies that have a high prevalence in the general population, explaining advanced treatment concepts and all aspects of assessment. Key clinical points are highlighted, and the text is supplemented with numerous informative figures and tables. The authors are respected experts, for the most part geriatric physicians, and the book is especially addressed to cardiologists, who may lack the described targeted information and treatment tools.
Keywords: Medicine.; Cardiology.; Nephrology.; Geriatrics.; Cardiac surgery.; elektronické knihy; electronic books